العلاقة بين الغياب الأبوي و اضطربات القلق لدى التلاميذ في سن الطفولة دراسة عيادية لخمس حالات - بلعربي زهراء; جودي مسعودة; خوحلي أحلام (My University, 2021)
Study title: (The relationship between parental absence and anxiety disorders among students in childhood.) The study aimed to identify the impact of the absence of the father on students in childhood, so that our study determines the quality of their anxiety and focus on its presence or not, as the study sample amounted to five cases Including two males and three females. We also used a set of tools to collect data, namely: Case Study.‌ The Black Foot Raesis by Louis Corman (lamb( We reached the following results: We found that there is anxiety in these children. Anxiety varies from case to case according to the lines of weakness and strength in the psychological employment of the child. The psychological structure of the child is affected by: the intensity of family cohesion, the presence of the parental image, the external environment, the relationship with the mother and the absence of the masculine model in the family